2020
DOI: 10.1111/jnc.15200
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory bulb‐targeted quantum dot (QD) bioconjugate and Kv1.3 blocking peptide improve metabolic health in obese male mice

Abstract: The olfactory system is a driver of feeding behavior, whereby olfactory acuity is modulated by the metabolic state of the individual. The excitability of the major output neurons of the olfactory bulb (OB) can be modulated through targeting a voltage‐dependent potassium channel, Kv1.3, which responds to changes in metabolic factors such as insulin, glucose, and glucagon‐like peptide‐1. Because gene‐targeted deletion or inhibition of Kv1.3 in the periphery has been found to increase energy metabolism and decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 94 publications
0
20
0
Order By: Relevance
“…While our interpretation cannot directly include olfactory ability (we cannot assume loss of OSNs = loss of olfactory ability), we and others have previously shown a relationship between metabolism and olfactory ability (Fadool et al 2004;Riera et al 2017). Kv1.3 −/− mice are notably super-smellers in terms of olfactory discrimination and threshold, are thin and are resistant to DIO (Xu et al 2003b(Xu et al , 2004Upadyay et al 2013;Thiebaud et al 2014;Riera et al 2017), and blocking Kv1.3 in the olfactory bulb causes a reduction in RER in the light cycle (Schwartz et al 2021). Mice with loss of olfactory ability due to genetic ablation of OSNs were found to have an increase in EE and be resistant to DIO (Riera et al 2017).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…While our interpretation cannot directly include olfactory ability (we cannot assume loss of OSNs = loss of olfactory ability), we and others have previously shown a relationship between metabolism and olfactory ability (Fadool et al 2004;Riera et al 2017). Kv1.3 −/− mice are notably super-smellers in terms of olfactory discrimination and threshold, are thin and are resistant to DIO (Xu et al 2003b(Xu et al , 2004Upadyay et al 2013;Thiebaud et al 2014;Riera et al 2017), and blocking Kv1.3 in the olfactory bulb causes a reduction in RER in the light cycle (Schwartz et al 2021). Mice with loss of olfactory ability due to genetic ablation of OSNs were found to have an increase in EE and be resistant to DIO (Riera et al 2017).…”
Section: Discussionmentioning
confidence: 81%
“…2017), and blocking Kv1.3 in the olfactory bulb causes a reduction in RER in the light cycle (Schwartz et al . 2021). Mice with loss of olfactory ability due to genetic ablation of OSNs were found to have an increase in EE and be resistant to DIO (Riera et al .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the Kv1.3 selectivity of HsTx1 over Kv1.1 was improved significantly by R14A substitution ( Rashid et al, 2014 ). In addition, peptide toxins are widely used to investigate the function of Kv1.x ion channels in various cell types in vivo as well as in vitro ( Erdogan et al, 2005 ; Tubert et al, 2016 ; Schwartz et al, 2020 ; Toldi et al, 2020 ). Obviously, one needs a reliable and economical system to produce an ample amount of these peptide toxins and their analogs to develop them as therapeutic drugs for the treatment of autoimmune disorders and to study the physiological role of ion channels.…”
Section: Discussionmentioning
confidence: 99%
“…The olfactory acuity is regulated by the metabolic state and therefore the olfactory system is a driver of feeding behavior. Enhancement of neuronal excitability of the major output neurons of the olfactory bulb via blocking voltage-dependent potassium channel reduces body weight in obese mice (Schwartz et al, 2021). Previous study suggested that chronic administration of fat in the diet impairs the spontaneous firing rate of MCs (Fadool et al, 2011), and reduces the amplitude of electro-olfactogram (EOG).…”
Section: Telencephalonmentioning
confidence: 99%